Genomic information in livestock has multiple uses in precision breeding and management. (2nd January 2019) - Berry, Donagh P
Abstract : Genomics is the study of the structure, function, evolution and mapping of genomes which comprises DNA. All cells have DNA which, in its interaction with the past and prevailing environment, influences animal performance. The DNA of an animal is inherited from its parents and does not change throughout the life of the animal. Hence, DNA provides a rich source of information on individual animals, which can be readily exploited in precision breeding and management decisions. Other than its use to augment the accuracy of estimating animal genetic merit, genomics can also be used in: parentage assignment; traceability; monitoring of major genes and congenital defects including karyotype disorders; estimating coancestry or inbreeding; quantifying breed composition; and facilitating more precise mating and management decisions. Generating genotype information on animals is now relatively inexpensive contributing to a high return on investment for farmers, breeders and even down-stream industries.